Hair Follicle Grafting Therapy Promotes Re-Emergence of Critical Skin Components in Chronic Nonhealing Wounds - Dyuti Saha; Sujaya Thannimangalath; Leelavathy Budamakuntla; Eswari Loganathan; Colin Jamora (Elsevier, 2021)
An exploding public health crisis is the exponential growth in the incidence of chronic nonhealing ulcers associated with diseases such as diabetes. Various modalities have been developed to stimulate wound closure that is otherwise recalcitrant to standard clinical treatments. However, these approaches primarily focus on the process of re-epithelialization and are often deficient in regenerating the full spectrum of structures necessary for normal skin function. Autologous hair follicle grafting is a recent therapy to stimulate the closure of such nonhealing wounds, and we observed effects beyond the epidermis to other important components of the dermis. We found that hair follicle grafting facilitated the reappearance of various undifferentiated and differentiated layers of the epidermis with the restoration of epidermal junctions. In addition, other important structures that are critical for cutaneous health and function such as the blood and lymph vasculature, nerve fibers, and sweat gland structures were restored in postgrafted wounds. Interestingly, both immune cells and inflammatory signals were substantially decreased, indicating a reduction in the chronic inflammation that is a hallmark of nonhealing wounds. Our observation that punch wounds created on the postgrafted area likewise healed suggests that this is a self-sustaining long-term therapy for patients with chronic wounds.